Pengembangan Database Evaluasi Kinerja Dosen Berbasis Android di STKIP PGRI Lubuklinggau - Armi Yuneti; Hamdan Hamdan; Donni Pestalozi; M. Rusni Eka Putra; Rudi Erwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to manage an android-based lecturer performance database. The approach in this study uses a systems approach with a waterfall model. The steps in developing the model are; 1) requirements analysis, 2) design, 3) implementation and unit testing. 4) integration and system test. The results of the study, the results of the database expert validation include; study programs, lecturers, courses, classes, students, and reports are appropriate to use. Website expert validation is carried out on 5 indicators, namely; a) content, b) readibility, c) speed, d) technological sophistication, and e) access worth using. Conclusion, Implementation of android-based lecturer performance database is feasible to use. Keywords: Android, Database, Lecturer Performance